Comparative Analysisi Of Export Competitiveness Of Indonesia Cocoa Beans To Malaysia Before And After The Export Duty Policy - Elda Septia (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2023)
The purpose of this study is to determine the comparative analysis of the competitiveness of Indonesian cocoa bean exports to Malaysia before and after the export duty policy. The research method used is descriptive quantitative method. The period studied is 2001 - 2020 or for twenty years. The data used for analysis in this study were obtained from the official website of the Central Bureau of Statistics, the United Nation Commodity Trade Statistics, the Food and Agriculture Organization of the United Nations, the Directorate General of Horticulture, and the Ministry of Trade of the Republic of Indonesia. The data analysis method used is Revealed Comparative Advantage (RCA), and the least square dummy variable (LSDV). The results of the RCA analysis of Indonesian cocoa exports to Malaysia before and after the export duty policy in 2001-2020 had a comparative competitiveness of >1. It can be concluded that overall the RCA of Indonesia's cocoa exports to Malaysia before and after the implementation of the export duty policy had differences, which can be seen from the average value of the RCA exports